Challenges in improving the minimal invasiveness of the surgical treatment for gastric cancer using robotic technology. Issue 5 (4th May 2021) - Kikuchi, Kenji; Suda, Koichi; Shibasaki, Susumu; Tanaka, Tsuyoshi; Uyama, Ichiro
Abstract: The number of operations performed using the da Vinci Surgical System ® (DVSS) has been increasing worldwide in the past decade. We introduced robotic gastrectomy for gastric cancer (GC) in January 2009 to overcome the disadvantage of conventional laparoscopic gastrectomy. Initially, we experienced some troubles in the technical aspect and cost of robotic surgery. After extensive trial and error, we were able to develop the "double bipolar method" and the "da Vinci's plane theory" to use DVSS effectively. We then conducted "Senshiniryo B, " which was a multi‐institutional prospective single‐arm study to determine the safety, feasibility, and effectiveness of robotic gastrectomy for GC in 2014. In that study, we demonstrated that the morbidity rate in the robotic group (2.45%) was significantly lower than that in the historical control group (6.4%). As a consequence of that clinical trial, 12 procedures, including robotic gastrectomy for GC, have been covered under the Japanese national insurance in 2018. An additional seven procedures were newly covered in April 2020. In the first half of this article, we describe the history of robotic surgery in the world and Japan and demonstrate the "double bipolar method" and "da Vinci's plane theory." In the latter half, we explain the Japanese systems for the safe dissemination of robotic surgery and state our efforts to solve some problems in robotic surgery. Abstract : In the first half of this article, we describe the history of robotic surgery in the world and Japan and demonstrate the "double bipolar method" and "da Vinci's plane theory." In the latter half, we explain the Japanese systems for the safe dissemination of robotic gastrectomy and state our efforts to solve some problems in robotic surgery.